The lament of an African: Book review Chirimuuta, R, & Chirimuuta, R (1987) AIDS, Africa and racism. London: Free Association Books. - Abdullah, Farud (PINS-Psychology in Society, 2025)
The discipline of medical sociology is a relatively new discipline compared to the other "sociologies", and rigorous academic work only found its feet in the 1950s with the work of Parsons. Radical critiques began to appear only in the 1970s as per lllich, the Ehrenreichs and Marxist writers such as Navarro, Waitzkin and others. There were exceptions of course, such as the writings of Virchow and indeed, of Engels himself in his The condition of the working class in England.